The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.bbamem.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Helix formation and stability in membranes

Abstract: In this article we review current understanding of basic principles for the folding of membrane proteins, focusing on the more abundant alpha-helical class. Membrane proteins, vital to many biological functions and implicated in numerous diseases, fold into their active conformations in the complex environment of the cell bilayer membrane. While many membrane proteins rely on the translocon and chaperone proteins to fold correctly, others can achieve their functional form in the absence of any translation appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
77
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 126 publications
5
77
2
Order By: Relevance
“…The resulting pattern of [ 2 H]Ala quadrupolar splitting (Dn q )m agnitudesi ndicates the core helix for R 8,16 GWALP23 is significantly tilted to give as imilart ransmembrane orientation in thinner bilayersw ith either saturated C12:0 or C14:0 acyl chains (1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC) or 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC)) or unsa-turatedC 16:1 D9 cis acyl chains. [1,[3][4][5]30] Previously we found that introducing as ingle arginine at position1 4i n GWALP23c aused the peptideh elix to rotate by 808 and to increase its tilt by 108 in DOPC bilayers, thus allowingt he arginine to gain access to the aqueous interface of the lipid bilayer. The inclusion of 10-20 mol %c holesterol in DOPC bilayers drives more of the R 8,16 GWALP23 helix population to the membrane surface, thereby allowing both charged arginines accesst ot he interfacial lipid head groups.T he resultss uggest that hydrophobic thickness and cholesterol content are more important than lipid saturationf or the argininep eptide dynamics and helix orientation in lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting pattern of [ 2 H]Ala quadrupolar splitting (Dn q )m agnitudesi ndicates the core helix for R 8,16 GWALP23 is significantly tilted to give as imilart ransmembrane orientation in thinner bilayersw ith either saturated C12:0 or C14:0 acyl chains (1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC) or 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC)) or unsa-turatedC 16:1 D9 cis acyl chains. [1,[3][4][5]30] Previously we found that introducing as ingle arginine at position1 4i n GWALP23c aused the peptideh elix to rotate by 808 and to increase its tilt by 108 in DOPC bilayers, thus allowingt he arginine to gain access to the aqueous interface of the lipid bilayer. The inclusion of 10-20 mol %c holesterol in DOPC bilayers drives more of the R 8,16 GWALP23 helix population to the membrane surface, thereby allowing both charged arginines accesst ot he interfacial lipid head groups.T he resultss uggest that hydrophobic thickness and cholesterol content are more important than lipid saturationf or the argininep eptide dynamics and helix orientation in lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Estimated to make up about3 0% of proteins encoded by the human genome, membranep roteins are the target of 50 %o fc urrent marketed drugs and are implicated in aw ide variety of disorders including Alzheimer's andP arkinson's diseases as well as cystic fibrosis. [1] Estimated to make up about3 0% of proteins encoded by the human genome, membranep roteins are the target of 50 %o fc urrent marketed drugs and are implicated in aw ide variety of disorders including Alzheimer's andP arkinson's diseases as well as cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane proteins play vital roles in numerous cellular processes including cell signaling, ion transport, and enzymedriven processes. [1] Estimated to make up about3 0% of proteins encoded by the human genome, membranep roteins are the target of 50 %o fc urrent marketed drugs and are implicated in aw ide variety of disorders including Alzheimer's andP arkinson's diseases as well as cystic fibrosis. [1,2] Am ore thorough understanding of the basic principles that govern membrane protein folding will improvet he ability to predict membrane protein structures and functions, anda ddress abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Estimated to make up about3 0% of proteins encoded by the human genome, membranep roteins are the target of 50 %o fc urrent marketed drugs and are implicated in aw ide variety of disorders including Alzheimer's andP arkinson's diseases as well as cystic fibrosis. [1,2] Am ore thorough understanding of the basic principles that govern membrane protein folding will improvet he ability to predict membrane protein structures and functions, anda ddress abnormalities. The constraints imposed by the lipid bilayer environment, nevertheless, presentc hallenges for determining the structures and lipid interactions of membrane proteins,r equirements necessary to elucidate disease mechanisms.…”
Section: Introductionmentioning
confidence: 99%